Early immune response regulated by a bone marrow mesenchymal stem cell model of multiple trauma in rats. (6th September 2018) - Wen, Tianlin; Meng, Hao; Wang, Fei; Chen, Yunqiang; Sun, Tiansheng
Aim: To explore whether transplantation of bone marrow mesenchymal stem cells (BMSCs) would reduce the immune response and protect vital organs in a rat model of femur shaft fracture combined with craniocerebral injury.Methods: The rats were divided into an experimental group (multiple traumas and receiving BMSCs injection, n = 25), a positive control group (only received the combination injuries, n = 25) and a negative group (n = 5).Results: Compared with the positive control group, plasma IL-6 and IL-8 were significantly lower at the early stage, and IL-10 was higher at the late period in the experimental group (p < 0.05). TNF-α ex-vivo synthesis descended quickly after trauma.Conclusion: BMSCs reduced the inflammatory response and were effective in immunomodulations during severe trauma.